1996
DOI: 10.1111/j.1445-2197.1996.tb00717.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Treatment Protocol for Patients With Chronic Radiation‐induced Rectal Bleeding

Abstract: Backgrounds and Methods:This study reviews the clinical features and reports the preliminary results of treatment of 34 consecutive patients with clinically significant bleeding from chronic, radiation-induced proctitis, using a combination of endoscopic YAG Laser and the application of topical formalin dressings to the rectal rnucosa. Results: Bleeding ceased in 25 patients (74%); bleeding continued but occurred only slightly and occasionally in five patients (15%); and three patients required operation to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
0
25
0
4
Order By: Relevance
“…[76][77][78][79][80][81][82][83] Data on use of the KTP laser for radiation proctitis still are limited, although, in 1 study, 65% of patients reported symptom improvement after 2 sessions. 84 Overall, approximately 80% to 88% of patients have marked reduction in daily rectal bleeding after a median of 3 sessions of laser treatment.…”
Section: Lasermentioning
confidence: 99%
“…[76][77][78][79][80][81][82][83] Data on use of the KTP laser for radiation proctitis still are limited, although, in 1 study, 65% of patients reported symptom improvement after 2 sessions. 84 Overall, approximately 80% to 88% of patients have marked reduction in daily rectal bleeding after a median of 3 sessions of laser treatment.…”
Section: Lasermentioning
confidence: 99%
“…a solução de formalina pode ser aplicada no reto basicamente de duas maneiras: por irrigação, quer de solução de formalina a 3,6 25 , 4 1,3,12,16,21,26 ou 5% 17 ; e uma outra técni-ca, proposta por Seow-choen et al 27 , é a aplicação direta com gaze embebida em formol, seja com solução a 4 1,4,6,[9][10][11][12]15,16,18,20,[26][27][28][29][30][31][32] ou 10% 2 . no presente trabalho, o controle da hemorragia foi atingido com a instilação endoluminal de formalina a 4 e 2%.…”
Section: Rev Bras Coloproct Janeiro/março 2011unclassified
“…Quando em contato com a mucosa, essa substância produz cauterização química local, determinando esclerose dos vasos com consequente melhora do sangramento 6,8,11,14 . após esse trabalho, surgiram várias publicações [1][2][3][4]6,9,[10][11][12][15][16][17][18][20][21][22][23][24][26][27][28][29][30][31][32] , em que os autores vêm tentando determinar a melhor técnica de aplicação, a concentração mais eficaz e identificar as complicações relacionadas com a sua aplicação. na Tabela 1, foram agrupadas, de forma comparativa, as diferentes séries de casos.…”
unclassified
“…Local application of 4% formaldehyde has been used with greater therapeutic success in some studies (Table 2). 12,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Evidence suggests that formalin is very effective in the treatment of CHRP, mainly in patients in whom the distal third of the rectum is affected. Other advantages of formalin application are low cost, low incidence of side-effects, ready availability, and easy application.…”
Section: Formalinmentioning
confidence: 99%